2008
DOI: 10.1177/104063870802000110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Retropharyngeal Lymph Node and Obex Region of the Brainstem in Detection of Chronic Wasting Disease in White-Tailed Deer (Odocoileus Virginianus)

Abstract: Chronic wasting disease (CWD) in Wisconsin was first identified in February 2002. By April 2005, medial retropharyngeal lymph node (RLN) tissues had been examined from over 75,000 white-tailed deer for the presence of CWD by either immunohistochemical (IHC) staining for the prion protein associated with CWD (PrP(res)) or by using enzyme-linked immunosorbent assays with confirmation of positives by IHC staining and had been detected in 469 animals. Obex tissue was also available from 438 of the CWD-positive ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 13 publications
3
50
1
Order By: Relevance
“…Based on this progression, the approximate stage of infection at harvest was determined for each CWDinfected animal as follows: 1) accumulation of PrP CWD in lymph node tissue only (henceforth referred to as lymph only); 2) accumulation of PrP CWD in lymph node tissue and the dorsal motor nucleus of the vagal nerve, but not in surrounding tissue (henceforth referred to as obex +); or 3) accumulation of PrP CWD in lymph node and throughout the obex (henceforth referred to as obex ++). Obex + is equivalent to obex scores 1 and 2; obex ++ is equivalent to obex scores 3 and 4 of Keane et al (2008a). To our knowledge, none of the CWD-positive deer in our study exhibited clinical signs of disease.…”
Section: Sample and Genetic Data Collectionmentioning
confidence: 55%
See 3 more Smart Citations
“…Based on this progression, the approximate stage of infection at harvest was determined for each CWDinfected animal as follows: 1) accumulation of PrP CWD in lymph node tissue only (henceforth referred to as lymph only); 2) accumulation of PrP CWD in lymph node tissue and the dorsal motor nucleus of the vagal nerve, but not in surrounding tissue (henceforth referred to as obex +); or 3) accumulation of PrP CWD in lymph node and throughout the obex (henceforth referred to as obex ++). Obex + is equivalent to obex scores 1 and 2; obex ++ is equivalent to obex scores 3 and 4 of Keane et al (2008a). To our knowledge, none of the CWD-positive deer in our study exhibited clinical signs of disease.…”
Section: Sample and Genetic Data Collectionmentioning
confidence: 55%
“…Retropharyngeal lymph nodes and the obex portion of the brainstem for all adults were sent to the Wisconsin Veterinary Diagnostic Laboratory, where CWD-infection status was determined using immunohistochemistry (Johnson et al, 2006;Keane et al, 2008a). A deer was determined to be CWD-positive at harvest if abnormal prions (PrP CWD ) were detected in lymph nodes or obex.…”
Section: Sample and Genetic Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Obex and retropharyngeal lymph nodes (RLN) are important tissues for CWD diagnosis, as PrP Sc is detectable in both tissues even at sub-clinical stages of CWD. 5 PrP C can be found throughout the body with higher concentrations at presynaptic membranes in the central nervous system (CNS). The exact physiological roles of PrP C are still under investigation, but many studies have suggested its participation in the metabolism of metals and its role as antioxidant (superoxide dismutase (SOD)-like activity).…”
Section: Introductionmentioning
confidence: 99%